PERLINDUNGAN HUKUM MEREK TERKENAL “CABERG” TERHADAP PENDAFTARAN MEREK “CABERG” LOKAL DI INDONESIA (STUDI KASUS PUTUSAN PENGADILAN NIAGA JAKARTA PUSAT NOMOR 06/Pdt.Sus-Merek/2020/ PN.Niaga.Jkt.Pst.) - Renald Saputra; R. Rahaditya (Jurnal Hukum Adigama, 2022)
Brands have very significant benefits in encouraging the quantity of existing brands, but it cannot bedenied that there are so many brands that give rise to various conflicts and disputes that occur becauseof these various brands. In general, conflicts on brands exist due to violations of existing brands withthe motivation to get easy profits and try, or imitate, even fake brands that exist in the community. Thisstudy discusses the legal protection of the well-known brand "caberg" against the registration of thelocal "caberg" trademark in Indonesia through a case study of the decision of the Central JakartaCommercial Court Number 06/pdt.sus-brand/2020/pn.niaga.jkt.pst. The author's reason for bringingup the case is that CABERG S.p.A. Italy is a well-known brand that must be protected. Ef orts toprovide legal protection for well-known marks have started with the Paris Convention. Theformulation of the problem in this study is how to regulate the principle of equality in principle whichis proposed in bad faith based on Law Number 20 of 2016 concerning Marks and GeographicalIndications? and How is the legal protection of the well-known brand "CABERG" against theregistration of the local "CABERG" mark in Indonesia related to the Decision of the Central JakartaCommercial Court Number 06/Pdt.Sus-Merek/2020/PN.Niaga.Jkt.Pst.? This study found that there areelements of similarity in principle or in whole to the well-known brand Caberg. There are similaritiesin the equation of form, writing method, sound equation and elemental equation.